2023
DOI: 10.3390/curroncol30020179
|View full text |Cite
|
Sign up to set email alerts
|

Relapsed/Refractory Multiple Myeloma: A Review of Available Therapies and Clinical Scenarios Encountered in Myeloma Relapse

Abstract: Multiple myeloma remains an incurable disease with the usual disease course requiring induction therapy, autologous stem cell transplantation for eligible patients, and long-term maintenance. Risk stratification tools and cytogenetic alterations help inform individualized therapeutic choices for patients in hopes of achieving long-term remissions with preserved quality of life. Unfortunately, relapses occur at different stages of the course of the disease owing to the biological heterogeneity of the disease. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 152 publications
1
9
0
1
Order By: Relevance
“…These results suggest that both ND and RR patients with high-GPRC5D-expression can expect strong therapeutic effect equivalent to CR with higher probability. Interestingly, our retrospective analysis revealed that a high-risk chromosome abnormality, t (4,14), provokes an increase of GPRC5D expression, which is consistent with a previous study on 48 MM patients in Vienna 5 . This indicates that GPRC5D targeted T cell-redirecting bispecific antibodies are applicable or even preferable for use in patients with high-risk chromosome abnormalities with high unmet medical needs.…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that both ND and RR patients with high-GPRC5D-expression can expect strong therapeutic effect equivalent to CR with higher probability. Interestingly, our retrospective analysis revealed that a high-risk chromosome abnormality, t (4,14), provokes an increase of GPRC5D expression, which is consistent with a previous study on 48 MM patients in Vienna 5 . This indicates that GPRC5D targeted T cell-redirecting bispecific antibodies are applicable or even preferable for use in patients with high-risk chromosome abnormalities with high unmet medical needs.…”
Section: Discussionsupporting
confidence: 92%
“… 57 In the current era of MM treatment, there are excellent treatment plans that can enable approximately 55% of patients to achieve at least 5 years of survival. 58 CAR-T cell therapy can cure some patients with high-grade lymphoma and invasive leukemia. But currently, in the field of MM, there is too little research data on this combination therapy, which is more based on hypotheses and small-scale single-center studies, and lacks a control group.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Se define como recaída a la recurrencia de enfermedad después de lograr un intervalo mayor a 60 días con respuesta al tratamiento previo. Se define como enfermedad refractaria a la ausencia de respuesta a tratamiento previo o a la progresión en los primeros 60 días posteriores a la última línea de tratamiento 27 . La progresión se debe tratar inmediatamente cuando sea identificada, en la tabla 7 se enumeran los criterios que obligan a tratar a un paciente.…”
Section: Tratamiento De Segunda Línea Y Progresión En Candidatos Y No...unclassified

Panorama actualizado en mieloma m�ltiple

Álvarez-Vera,
Alvarado-Ibarra,
de la Peña-Celaya
et al. 2023
REMQ